(3JSdje GdeLQejf habkG dCMcGe GdbGfhf GdEJMGOj Qbe (B39 (3dSfI (B2009 (3dOhdI GdEeGQGJ GdYQHjI GdeJMOI(B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3eMeO Ydj eMeO YHjO GdeMhGK GdMehOjs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JfGhdJ aj GdQSGdI ehVhY JSdje GdeLQejf HGYJHGQg GHQR eXGgQ GdJYGhf GdOhdi ecGaMI GdXGgQI GdGLQGejI (B. (3hbO JfGhdJ JSdje GdeLQejf hab GMcGe GdbGfhf GdGJMGOj GdGeGQGJj Qbe (B39 (3dSfI (B2006 (3GdPj jfXe GdJYGhf GdbVGFj GdOhdi aj GdeSGFd GdLfGFjI hPdc aj GWGQ ef GdOQGSI GdJMdjdjI GdebGQfI(B.(3h bO bSeJ GdQSGdI Gdi HGHjf GdGhd jJfGhd GdGWGQ GdehVhYj dfXGe JSdje GdeLQejf hGdKGfj jJfGhd GdGWGQ GdGLQGFj dfXGe JSdje GdeLQejf (B. (3hbO bSeJ GdHGH GdGhd Gdi GQHYI aUhd GdGhd jJfGhd eGgjI fXGe JSdje GdeLQejf hGdKGfj jJfGhd eUGOQ GdGdJRGe GdbGfhfj ddJSdje hGdKGdK jJfGhd GdGKGQ GdehVhYjI ddJSdje hGdQGHY jJfGhd GdLQGFe GdJi jLhR HgG GdJSdje (B. (3hbO bSeJ GdHGH GdKGfj Gdi GQHYI aUhd GdGhd jJfGhd GdfXGe GdGLQGFj dJSdje GdeLQejf hGdKGfj jJfGhd GdTQhW GdGLQGFjI dJSdje GdeLQejf hGdKGdK jJfGhd GdVeGfGJ GdNGUI HELQGAGJ GdJSdje hGdQGHY jJfGhd GdGKGQ GdGLQGFjI ddJSdjes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2014s
(3HHdjhLQGajG(B: (3UaMGJ (B396-415s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVeGfGJ GdNGUI HGLQGAGJ JSdje GdeLQejfs; (3GdVeGfGJ GdGLQGFjI hGdTNUjIs; (3GdVeGfGJ GdNGUI HGdYbhHIs; (3GdVeGfGJ GdNGUI HGdeMGceIs; (3WdH JSdje GdeLQejfs; (3GdJLQje GdeROhLs; (3eHOG GdeYGedI HGdeKds; (3GdbGfhf GdLfGFj GdGeGQGJjs; (3GdbGfhf GdLfGFj GdOhdjs; (3QSGFd LGeYjIs -- (3cdjI GdMbhbs -- (3LGeYI GdbGgQIs